Hesperidin increase cytotoxic effect of doxorubicin in MCF-7 cells - Hermawan, Adam; Meiyanto, Edy; Susidarti, Ratna Asmah (Indonesian Journal of Pharmacy, 2010)
Hesperidin,  a  flavonoid,  shows  strong  cytotoxic  effect  in  several  cancer cell  lines.  The  aim  of  this  research  was  to  investigate  cytotoxic  activities  of hesperidin  alone  and  in  combination  with  doxorubicin.  Cell  viability  assay  of hesperidin,  doxorubicin,  and  combination  treatments  were  carried  out  by  using MTT  assay.  Apoptosis  assay  was  done  using  double  staining  method  using Ethidium  Bromide-Acridine  Orange.  Hesperidin  did  not  show  cytotoxic  effect but doxorubicin showed cytotoxic effect with IC50467 nM. Hesperidin (5, 50 and 100  µM)  increased  cytotoxic  effect  of  doxorubicin  compared  with  doxorubicin alone.  The  strongest  cytotoxic  activity  was  showed  by  the  combination  of  200 nM  doxorubicin  and  100  µM  hesperidin.  Combination  treatment  of  doxorubicin 200  nM  and  hesperidin  100  µM  induced  apoptosis  in  MCF-7 cells.  Hesperidin  is potentially  to  be  developed  as  co-chemotherapeutic  agent  for  breast  cancer, while molecular mechanism need to be explored.Key words: Hesperidin, doxorubicin, synergism, MCF-7, apoptosis